INHERITANCE OF RESISTANCE TO PStV IN TRANSGENIC PEANUTS CONTAINING cp PStV GENE - ., Dwi Hapsoro, Hajrial Aswidinnoor, Rusmilah Suseno, Jumanto, dan Sudarsono (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Inheritance of Resistance to PStV in Transgenic Peanuts Containing cp PStV Gene. We have obtained transgenic peanut lines containing coat protein gene of PStV. To get maximal use of the transgenic character in a breeding program, it is necessary that the transgene is also stably inherited and expressed. This experiment was conducted from June 2002 – January 2005 at Plant Molecular Biology Laboratory, Bogor Agricultural University, and Queensland Agricultural Biotechnology Center, The University of Queensland, Australia. The research aimed (1) to test whether PStV cp transgene was functional in progenies derived from crosses between transgenic peaanut plants containing PStV cp gene and non-transgenic ones and (2) to determine pattern of inheritance of resistance to PStV as a result of PStV cp gene action. Several crosses were made between trangenic peanut cv.Gajah resistant to PStV (T4 generation) and non-transgenic peanut line WS susceptible to PStV. The F1 and F2 populations were mechanically inoculated with PStV two weeks after planting. The experiment showed that all plants in the F1 population were less susceptible to PStV, suggesting that the transgene was partially dominant. Phenotipic segregation in F2 population was not Mendelian with the appearance of quick and slow recovery plants and the number of resistant plants being more than expected. However, the proportion of transgenic and non-transgenic plants followed 3:1 ratio, which was Mendelian.